Proteomic alterations underlie an association with teratozoospermia in obese mice sperm - Yuanhong Peng; Wenzhen Zhao; Fei Qu; Jia Jing; Yanqin Hu; Yue Liu; Zhide Ding (BMC, 2019)
Abstract Background Obesity is a worldwide crisis impairing human health. In this condition, declines in sperm quality stem from reductions in sperm concentration, motility and increase in sperm deformity. The mechanism underlying these alterations remains largely unknown. This study, determined if obesity-associated proteomic expression patterns in mice sperm parallel those in spermatozoa obtained from obese humans. Methods An obese mouse model was established via feeding a high-fat diet (HFD). Histological analysis identified testicular morphology and a computer assisted semen analyzer (CASA) evaluated sperm parameters. Proteome analysis was performed using a label-free quantitative LC-MS/MS system. Western blot, immunohistochemical and immunofluorescent analyses characterized protein expression levels and localization in testis, sperm and clinical samples. Results Bodyweight gains on the HFD induced hepatic steatosis. Declines in sperm motility accompanied sperm deformity development. Differential proteomic analysis identified reduced cytoskeletal proteins, centrosome and spindle pole associated protein 1 (CSPP1) and Centrin 1 (CETN1), in sperm from obese mice. In normal weight mice, both CSPP1 and CETN1 were localized in the spermatocytes and spermatids. Their expression was appreciable in the post-acrosomal region parallel to the microtubule tracks of the manchette structure in spermatids, which affects spermatid head shaping and morphological maintenance. Moreover, CSPP1 was localized in the head-tail coupling apparatus of the mature sperm, while CETN1 expression was delimited to the post-acrosomal region within the sperm head. Importantly, sperm CSPP1 and CETN1 abundance in both the overweight and obese males decreased in comparison with that in normal weight men. Conclusion These findings show that regionally distinct expression and localization of CETN1 and CSPP1 is strongly related to spermiogenesis and sperm morphology maintaining. Obesity is associated with declines in the CETN1 and CSPP1 abundance and compromise of both sperm morphology in mice and relevant clinical samples. This parallelism between altered protein expression in mice and humans suggests that these effects may contribute to poor sperm quality including increased deformity.